2014
DOI: 10.1097/moh.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia in the newborn

Abstract: PURPOSE OF REVIEW Review normal blood neutrophil concentrations and the clinical approach to neutropenia in the neonatal period. A literature search on neonatal neutropenia was performed using the databases PubMed, EMBASE, and Scopus and the electronic archive of abstracts presented at the annual meetings of the Pediatric Academic Societies. RECENT FINDINGS This review summarizes current knowledge on the causes of neutropenia in premature and critically-ill neonates, focusing on common causes such as materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 84 publications
(74 reference statements)
2
37
0
4
Order By: Relevance
“…We used the maximum (creatinine) or minimum (platelet count, ANC) value recorded when multiple laboratory results were available on a given day. We defined neutropenia as ANC <1000 cells/μL, 11 thrombocytopenia as platelet count <100,000/μL, 12 and abnormal renal function as serum creatinine ≥1.3 mg/dL. 13 …”
Section: Methodsmentioning
confidence: 99%
“…We used the maximum (creatinine) or minimum (platelet count, ANC) value recorded when multiple laboratory results were available on a given day. We defined neutropenia as ANC <1000 cells/μL, 11 thrombocytopenia as platelet count <100,000/μL, 12 and abnormal renal function as serum creatinine ≥1.3 mg/dL. 13 …”
Section: Methodsmentioning
confidence: 99%
“…If the neonate is severely neutropenic and there is concern about the risk of severe infections, G-CSF may be helpful in this specific setting. [37] A recently published, large, retrospective study of 348 neonatal intensive care units with 30,705 neutropenic infants, 2142 treated with G-CSF (7%), showed that G-CSF shortened the time for hematological recovery but did not reduce secondary sepsis or death at 14 days compared to untreated infants. [38] Thus the specific cause for neutropenia and other clinical factors should be considered in all cases.…”
Section: Pregnancymentioning
confidence: 99%
“…Furthermore, ANCs < 1,000/μl is frequently seen at neonatal intensive care units, especially in preterm infants. Neutropenia in a neonate is mostly due to non-immune causes including sepsis, low birth weight, and pregnancy-induced maternal hypertension (table 2) [54,55,56]. Clinicians should consider further evaluation of neonatal neutropenia if no clear underlying cause is present and/or if the ANC does not increase within 3-5 days.…”
Section: Diagnosismentioning
confidence: 99%